PENGARUH INFLASI, PRODUK DOMESTIK BRUTO, DAN NILAI TUKAR RUPIAH ATAS YUAN TERHADAP INDEKS HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (SUBSEKTOR MAKANAN DAN MINUMAN) - ANJELA, LITA B1021131012 (Jurnal Manajemen Update, 2018)
The purpose of this research is to analize about the impact of Inflation rate, Gross Domestic Product, and Exchange Rate (IDR/CNY) on the sectoral index of Manufacturing Firms Listed in Indonesia Stock Exchange (Food and Beverage Subsector). This research applies quantitative research method, using quarterly data which one selected by employies the purposive sampling technique. Some 12 firms are selected as sample for the period 2011-2016.Employing panel data, the total number of data accurats for 288 firm-year observation. Panel regression model using Random Effect Model (REM) and Error Component Model (ECM) approach is used to estimate cooperation if the regression.Research should that inflation rate, GDP, and exchange rate affects positively and significantly are stock index food sectoral, the firms balancing to food and beverage sector. Influence that inflation explains the first hypothesis is not approve with the formulation of hypotheses that researcher have proposed, while influence positive explains twice and third hypothesis is approve with the formulation of hypotheses that researcher have proposed.Keywords: Inflation, Gross Domestic Product, Exchange Rate (IDR/CNY), and Manufacture Stock Price